A Novel Quasi-Open Loop Architecture for GNSS Carrier Recovery Systems. (3rd June 2012) - Tahir, Muhammad; Presti, Letizia Lo; Fantino, Maurizio
Abstract : The problem of designing robust systems to track global navigation satellite system (GNSS) signals in harsh environments has gained high attention. The classical closed loop architectures, such as phase locked loops, have been used for many years for tracking, but in challenging applications their design procedure becomes intricate. This paper proposes and demonstrates the use of a quasi-open loop architecture to estimate the time varying carrier frequency of GNSS signals. Simulation results show that this scheme provides an additional degree of freedom to the design of the whole architecture. In particular, this additional degree of freedom eases the design of the loop filter in harsh environments.